Single versus multi species indicators in environmental modelling: a review [CD-ROM] - Shanmuganathan, S; Singh, VP; Yudav, RN; Sallis, P; Buckeridge, J (Council of Scientific and Industrial Research (CSIR), 2003)
The use of biological responses in environmental modelling, also referred to as biomonitoring, mainly involves indicator species or communities those accumulate pollutants in their tissues from the surrounding environment, thus reflect the environmental conditions. Despite the progress made through research activities in detecting biological changes in these organisms at various levels i.e. macromolecular, cellular within individual organisms and in communities, constraints with conventional data analysis methods in exactly assessing an environmental pollution and its real cause led ecologists to experiment with emerging technologies. The recent use of artificial neural networks (ANNs), especially self-organising map (SOM) and evolving SOM techniques to analyse multi dimensional data sets provide a means to analyse community dynamics and is elaborated upon with a case study from northern New Zealand.